If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -2(x + -6) = 4(x + 1) + 2 Reorder the terms: 6x + -2(-6 + x) = 4(x + 1) + 2 6x + (-6 * -2 + x * -2) = 4(x + 1) + 2 6x + (12 + -2x) = 4(x + 1) + 2 Reorder the terms: 12 + 6x + -2x = 4(x + 1) + 2 Combine like terms: 6x + -2x = 4x 12 + 4x = 4(x + 1) + 2 Reorder the terms: 12 + 4x = 4(1 + x) + 2 12 + 4x = (1 * 4 + x * 4) + 2 12 + 4x = (4 + 4x) + 2 Reorder the terms: 12 + 4x = 4 + 2 + 4x Combine like terms: 4 + 2 = 6 12 + 4x = 6 + 4x Add '-4x' to each side of the equation. 12 + 4x + -4x = 6 + 4x + -4x Combine like terms: 4x + -4x = 0 12 + 0 = 6 + 4x + -4x 12 = 6 + 4x + -4x Combine like terms: 4x + -4x = 0 12 = 6 + 0 12 = 6 Solving 12 = 6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 9*(3+4)= | | 1.5x+3y-z=-8 | | x-x*0.1=86.96 | | -5(1)=8+4m | | x(5+x)=(x*x)+3x+1 | | 12q-4=32 | | 2(3x-4)+5-4x=11 | | 24x+1.8-x+3=16-1 | | 16x=.6x | | 0.8(x-5)=0.4x-20 | | -Rx+5y=-T | | 7x+-5=4x+4 | | 24x+1*8-x+3=16-1 | | f(x)=x(x+1)(x-6) | | -5(0)=8+4m | | (M+3)(m-4)= | | 56+12x=8+8x | | D=2abc | | 1.5r+15=45r | | -3X+10+4X=13 | | 2ax=10a-3ax | | 8y+8=7y-12 | | 4t-2=33-3y | | 7m+38=5m-16 | | 3y=9-4x | | 3c+17=8 | | 3x-8x-5=-15 | | 5x-17=3x+4 | | 4q+3=-9 | | p-4+-9=p | | 2x(x+3)-7=5(5-x)+7(x+1) | | -5c(4c^2-2c)= |